Intake of animal protein blend plus carbohydrate improves body composition with no impact on performance in endurance athletes - Naclerio, F.; Larumbe-Zabala, E.; Larrosa, M.; Centeno, A.; Esteve-Lanao, J.; Moreno-Pérez, D. (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
The impact of animal protein blend supplements in endurance athletes is scarcely researched. The authors investigated the effect of ingesting an admixture providing orange juice and protein (PRO) from beef and whey versus carbohydrate alone on body composition and performance over a 10-week training period in male endurance athletes. Participants were randomly assigned to a protein (CHO + PRO, n = 15) or a nonprotein isoenergetic carbohydrate (CHO, n = 15) group. Twenty grams of supplement mixed with orange juice was ingested postworkout or before breakfast on nontraining days. Measurements were performed pre- and postintervention on body composition (by dual-energy X-ray absorptiometry), peak oxygen consumption (VO2peak), and maximal aerobic speed. Twenty-five participants (CHO + PRO, n = 12; CHO, n = 13) completed the study. Only the CHO + PRO group significantly (p < .05) reduced whole-body fat (mean ± SD) (-1.02 ± 0.6 kg), total trunk fat (-0.81 ± 0.9 kg), and increased total lower body lean mass (+0.52 ± 0.7 kg), showing close to statistically significant increases of whole-body lean mass (+0.57 ± 0.8 kg, p = .055). Both groups reduced (p < .05) visceral fat (CHO + PRO, -0.03 ± 0.1 kg; CHO, -0.03 ± 0.5 kg) and improved the speed at maximal aerobic speed (CHO + PRO, +0.56 ± 0.5 km/hr; CHO, +0.35 ± 0.5 km/hr). Although consuming animal protein blend mixed with orange juice over 10 weeks helped to reduce fat mass and to increase lean mass, no additional performance benefits in endurance runners were observed.